Blunt laryngeal trauma secondary to sporting injuries. Issue 8 (9th June 2017) - Mendis, D; Anderson, J A
Abstract: Background: Laryngeal injury after blunt trauma is uncommon, but can cause catastrophic airway obstruction and significant morbidity in voice and airway function. This paper aims to discuss a case series of sports-related blunt laryngeal trauma patients and describe the results of a thorough literature review. Method: Retrospective case-based analysis of laryngeal trauma referrals over six years to a tertiary laryngology centre. Results: Twenty-eight patients were identified; 13 (46 per cent) sustained sports-related trauma. Most were young males, presenting with dysphonia, some with airway compromise (62 per cent). Nine patients were diagnosed with a laryngeal fracture. Four patients were managed conservatively and nine underwent surgery. Post-treatment, the majority of patients achieved good voice outcomes (83 per cent) and all had normal airway function. Conclusion: Sports-related neck trauma can cause significant injury to the laryngeal framework and endolaryngeal soft tissues, and most cases require surgical intervention. Clinical presentation may be subtle; a systematic approach along with a high index of suspicion is essential, as early diagnosis and treatment have been reported to improve airway and voice outcome.